Focus on Vitamin D and the Adrenal Gland - Muscogiuri, G.; Altieri, B.; Penna-Martinez, M.; Badenhoop, K. (Hormone and Metabolic Research, 2015)
The main role of vitamin D is to maintain calcium and phosphorus homeostasis, thus preserving bone health. However, recent evidences have demonstrated that vitamin D may also play a role in a variety of nonskeletal disorders such as endocrine diseases and in particular type 1 diabetes, type 2 diabetes, adrenal diseases, and the polycystic ovary syndrome. Despite controversial results on an association of low vitamin D levels with cortisol and aldosterone overproduction, encouraging in vitro findings have been reported on vitamin D effects in adrenocortical cancer cells. The focus of this review is the role of vitamin D in adrenal diseases and the results of vitamin D supplementation studies in patients. Although many studies support a beneficial role of vitamin D in adrenal disease, randomized controlled trials and mechanistic studies are required to provide more insight into the efficacy and safety of vitamin D as a therapeutic tool.
Keywords: rapid vitamin D action; Cushing’s syndrome; adrenal cancer; primary hyperaldosteronism; Addison’s disease